Design and Implementation of a Virtual Laboratory for the Analysis and Synthesis of Mechanisms - Mejia Calderón, Luz Adriana; Romero Piedrahita, Carlos Alberto (Ingeniería, 2025)
Context: This paper presents the design and implementation of a virtual laboratory developed as a pedagogical support tool for courses in mechanisms analysis and synthesis within Mechanical Engineering programs. Method: Our virtual laboratory was developed using GeoGebra, Moodle, and Matlab. The design methodology was structured into four key stages: requirements analysis, conceptual design, content development, and implementation and evaluation. Results: The outcome is a comprehensive virtual laboratory framework comprising 12 interactive exercises focused on the analysis and synthesis of planar mechanisms. This paper outlines the functional features of the virtual laboratory, including its graphical user interface, user guide, instructional practices, and assessment procedures – demonstrating its value as an effective tool to support and enhance both teaching and student learning. Conclusions: The virtual laboratory allowed students to conceptualize through the visualization of kinematic and dynamic variables, offering a complementary and interactive alternative to traditional theoretical instructions. This aligns with active learning strategies, as the teacher reported greater student engagement. Students advanced at their own pace through the exercises and were able to observe how geometric and functional modifications in mechanisms influence their kinematic and dynamic behavior.